Tác động của nhận thức sự hỗ trợ của tổ chức tới ý định nghỉ việc: Vai trò điều tiết của vốn tâm lý - Nguyễn Hồng, Quân; Lê Ngọc, Hân; Lã Hương, Ly; Trần Thị Quỳnh, Chi; Trần Thị Yến, Nhi; Nguyễn Minh, Phương (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study aims to measure the impact of perceived organizational support on turnover intention and affective commitment, with psychological capital as a moderator, based on the Conservation of Resources Theory and Social Exchange Theory. Data were collected from 301 employees, including newcomers and those in career development or stabilization stages, using a non-probability random sampling approach. Findings reveal that perceived organizational support positively influences affective commitment, with psychological capital playing a crucial role in reinforcing this relationship. This study also shows that affective commitment negatively correlates with turnover intention, as does perceived organizational support. The study proposes managerial implications to enhance commitment, reduce turnover intention, and optimize the impact of psychological capital on employee engagement.
Keywords: Perceived organizational support; Affective commitment; Turnover intention; Psychological capital